1997
DOI: 10.1177/073401689702200205
|View full text |Cite
|
Sign up to set email alerts
|

Complaints Against the Police: A Focus Group Study of Citizen Perceptions, Goals, and Expectations

Abstract: This article explores citizen perceptions, goals, and expectations in filing complaints against the police. It is based on 10 focus groups representing a cross-section of a medium-sized midwestern community. Its findings confirm earlier research indicating a poor "fit" between complainant goals and complaint procedures. Although most existing complaint procedures are designed to investigate complaints of officer misconduct and to punish guilty officers, relatively few of the focus group participants indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 11 publications
3
68
1
Order By: Relevance
“…''They are more willing to answer questions knowing they will not be deported'' (Herbst & Walker, 2001, p. 338). A focus group in one midwestern city found that Hispanics had little understanding of the police complaints process and were generally fearful that police contacts could result in immigration or employment problems (Walker, 1997).…”
Section: Hispanics and The Policementioning
confidence: 99%
“…''They are more willing to answer questions knowing they will not be deported'' (Herbst & Walker, 2001, p. 338). A focus group in one midwestern city found that Hispanics had little understanding of the police complaints process and were generally fearful that police contacts could result in immigration or employment problems (Walker, 1997).…”
Section: Hispanics and The Policementioning
confidence: 99%
“…Indeed, Brown (1987Brown ( , 1988 and Prenzler (2004) suggest that complainants whose claims were unsubstantiated were in turn dissatisfied with the civilian review board. Walker (1998) presents a compelling explanation for this phenomenon. He explains that being confirmed by the board brings a sense of achievement for complainants.…”
Section: Discussionmentioning
confidence: 91%
“…In fact, age has been regarded as an important demographic variable in determining perceptions of police (Brown & Benedict, 2002;Cao, Frank, & Cullen, 1996;Webb & Marshall, 1995). By exploring citizen perceptions and the goals and expectations of the police, Walker (1997) found older Hispanics have a high degree of deference for the police. Further, when juvenile perceptions of the police were studied, Borrero (2001) found African American and Latino 2 youth who lived in disadvantaged neighborhoods had negative views toward police because they often experienced police misconduct against them (see also Solis, Portillos, & Brunson, 2009).…”
Section: Demographic Characteristicsmentioning
confidence: 96%
“…In fact, Mexicans accounted for a disproportionate percentage of Immigration and Customs Enforcement (ICE) detentions and deportations in 2011 (Simanski & Sapp, 2012). Due to the threat of deportation, immigrants may avoid contacting law enforcement officials even if they have been victimized (Menjivar & Bejarano, 2004;Walker, 1997). For instance, a recent study found that being questioned about one's immigration status is likely to lead to lower confidence levels in the police among Hispanic immigrants (Barrick, 2014).…”
Section: Immigrant-specific Factorsmentioning
confidence: 96%